ЭКОЛОГИЯЛЫҚ МӘДЕНИЯТТЫ ҚӘЛИПЛЕСТИРИЎДЕ ХАЛЫҚ ПЕДАГОГИКАСЫНАН ПАЙДАЛАНЫЎ УСЫЛЛАРЫ - Досходжаева, А. (SCIENCE and SOCIETY, 2016)
The article considers the importance of folk Pedagogy in the formation of ecological culture, preventing and solution of environmental problems. Folk Pedagogy reflects the culture and spiritual education of certain particular people. Ecological culture is widely highlighted in the folklore.